2009
DOI: 10.5539/ass.v5n7p70
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Collaborative Learning among Malaysian Undergraduates

Abstract: This study was to investigate Malaysian undergraduates' preference for collaborative learning activities that were carried out during English lessons. Gender, location and programme were studied in order to determine their influence on the undergraduates' preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 11 publications
3
18
0
Order By: Relevance
“…Thus, Maesin et al (2009) call for a need for English teachers to ensure enough opportunities for students to use English in discussing and communicating with each other efficaciously inside the language learning classroom. More importantly, students find it difficult to utilize the language skills either inside or outside the language classroom owning to inadequate opportunities and poor language learning environment (see Sect.…”
Section: Problems In the Chinese Efl Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Maesin et al (2009) call for a need for English teachers to ensure enough opportunities for students to use English in discussing and communicating with each other efficaciously inside the language learning classroom. More importantly, students find it difficult to utilize the language skills either inside or outside the language classroom owning to inadequate opportunities and poor language learning environment (see Sect.…”
Section: Problems In the Chinese Efl Educationmentioning
confidence: 99%
“…Maesin et al (2009) argue that the likelihood of critical thinking is dictated by the learning environment and the teaching approach used. Maesin et al (2009) argue that the likelihood of critical thinking is dictated by the learning environment and the teaching approach used.…”
Section: Allow For Critical Thinkingmentioning
confidence: 99%
“…Maesin (2006) reported that the participants of her study at UiTM University, regardless of being from urban or rural areas, equally preferred collaborative learning. In a similar study by Maesin, Mansor, Shafie, and Nayan (2009) among 162 Malaysian science and social science undergraduates at the Universiti Technologi MARA (UiTM) Perlis, it was found that almost all of the participants (male & female) preferred collaborative learning activities during their English lessons. The results of a study by Kamsah and Talib (2003) among the lecturers and the final year students at the faculty of Chemical and Natural Resources Engineering at the University of Technology Malaysia Skudai indicated that the participants unanimously agreed on the importance of group work activities in classrooms.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, one of major concerns in Malaysian second language learning research is second language learning environment. As mentioned by Maesin et al (2009), "in second language learning, students find difficulties to utilize the language skills outside of language classrooms as there are fewer opportunities to do so due to poor language environments" (p.71).…”
Section: Introductionmentioning
confidence: 99%